2022
DOI: 10.3390/designs6060119
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Structural Features of Lignocellulosic Materials and Ethanol Production Yield

Abstract: Lignocellulosic materials are a mixture of natural polymers which can be considered a great alternative source of chemical products and energy. Hence, pinewood, poplar wood, and rice straw, as representatives of different types of lignocelluloses, were subjected to several pretreatment types in order to increase ethanol production yield. All pretreatments increased enzymatic hydrolysis and ethanol yield, specifically pretreatment with phosphoric acid. This pretreatment increased ethanol yields by 304.6% and 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In the literature, the composition of the resulting hydrolysate used for cultivations is rarely given; mostly cellulose conversion rates are indicated. Bay et al obtained glucose yields between 44.6 and 49.3% from poplar and pine wood as well as rice straw after phosphoric acid treatment and enzymatic hydrolysis (Bay et al 2022 ). Cui et al report glucose yields of up to 46.3% from paper mulberry ( Broussonetia papyrifera ) after pretreatment with deep eutectic solvents at elevated temperatures followed by saccharification (Cui et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the composition of the resulting hydrolysate used for cultivations is rarely given; mostly cellulose conversion rates are indicated. Bay et al obtained glucose yields between 44.6 and 49.3% from poplar and pine wood as well as rice straw after phosphoric acid treatment and enzymatic hydrolysis (Bay et al 2022 ). Cui et al report glucose yields of up to 46.3% from paper mulberry ( Broussonetia papyrifera ) after pretreatment with deep eutectic solvents at elevated temperatures followed by saccharification (Cui et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…All of this indicates that deacetylated biomass positively influences the overall process. However, Bay et al [53] reported that the removal of those acetyl groups with an alkaline PT will limit enzyme accessibility and partially depolymerize glucose, which then highlights the importance of further understanding the influence of xylose acetylation on the efficiency of the bioconversion process. Finally, when it comes to the PT's duration, coupling either high temperature and short treatment time (e.g., 270 • C, 1 min) or low temperature and long duration time (e.g., 190 • C-10 min) has been highlighted as a way to effectively solubilize hemicelluloses [26,107].…”
Section: Thermomechanical Pretreatmentsmentioning
confidence: 99%
“…Over the years, various chemical PTs have been tested on woody lignocellulosic biomasses. For instance, five different chemical solvents were used for the PT of poplar wood (hardwood), pine wood (softwood), and rice straw (herbaceous) [53]. In this study, the samples were subjected to distilled water (180 • C, 30 min), dilute sulfuric acid (H 2 SO 4 , 0.5% w/w H 2 SO 4 /H 2 O), concentrated phosphoric acid (H 3 PO 4 , 85% w/w H 3 PO 4 /H 2 O), sodium hydroxide (NaOH, 2 M), and sodium carbonate (Na 2 CO 3 , 0.5 M).…”
Section: Chemical Pretreatmentsmentioning
confidence: 99%
See 2 more Smart Citations